Impact of Willem Einthoven (1860-1927) and his contemporary Nobel prize laureates on present day medical technology: ECG and Leyden (Salud y Ciencia, 2025)
The discovery of animal electricity by the Italian physician-scientist Luigi Galvani (1737-1798) was the starting point for the broad discipline of electrophysiology, with important implications in cardiology and neurosciences. Later, following the recording by Waller of the electrical activity originating from the canine heart, Einthoven succeeded in obtaining sensitive measurements allowing for detailed interpretation of cardiac abnormalities observed in humans. Nowadays, the field embraces integrated advanced medical imaging modalities, as well as enrichment based on artificial intelligence. This survey briefly covers three centuries of bioelectricity, reaching a summit with reliable measurements and clinical interpretation of the electrocardiogram (ECG) by Willem Einthoven at Leyden University, for which efforts he was awarded the 1924 Nobel Prize for Physiology or Medicine.